KAJIAN SUBSTITUSI TEPUNG TERIGU DENGAN PASTA JAGUNG MANIS (Zea mays saccharata sturt) PADA PEMBUATAN KUE BINGKE - Riko Imanuel; Suko Priyono; Lucky Hartanti (Universitas Tanjungpura, 2019)
Bingke was a traditional cake that resembles a kue lumpur that was made of wheat flour, sugar, milk, coconut milk, egg, and salt. The purposes of this research were to know the best substitution of wheat flour and sweetcorn pasta in the making of Bingke cake and to find out the product of sweetcorn composition that the most preferred of consumers. This research used a randomized complete block design (RCBD) one factor that was the ratio of formulation between wheat flour and sweetcorn pasta was repeated four times by six levels. The observing parameters were measured of water content, developmental power and sensory. The data obtained were analyzed by the ANOVA test of a 5% test level. The results showed the best treatment for Bingke 15 g sweetcorn and 10 g wheat flour, water content 63.53% and developmental power 8.75%. The sensory characteristics of sweetcorn Bingke were the taste 4.0 (like), sweetness level 4.1 (like), texture 4.3 (like), and preference 4.4 (like).